Fabrication of Tamarindus indica seeds extract loaded-cream for photo-aged skin: Visioscan® studies - Waqas, Muhammad Khurram; Khan, Barkat Ali; Akhtar, Naveed; Chowdhry, Farzana; Khan, Haroon; Bakhsh, Sattar; Khan, Shahzeb; Rasul, Akhtar (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Intracellular and extracellular oxidative stress triggered by free radicals promotes skin aging, which is designated by atypical pigmentation and wrinkles. The consumption of antioxidants is an efficacious measure to avert symptoms involved in skin aging. Aim: The current research was commenced to explore the anti-aging potential of antioxidants present in Tamarindus indica seeds extract. Material and methods: Tamarindus indica seeds extract was obtained by concentrating the ethanolic extract of seeds. The antioxidant activities of the extract were measured by nitric oxide radical scavenging assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, hydroxyl radical scavenging assay and superoxide radical scavenging assay. Formulation comprising 4% of the concentrated extract of seeds was formulated by loading it in the internal aqueous phase of water-in-oil (W/O) cosmetic emulsion. The base, used as control, consisted of the same emulsion but without loading Tamarindus indica seeds extract. The cosmetic emulsions were applied to the cheeks of 11 healthy male volunteers for duration of 12 weeks. Both base and formulation were assessed for their antioxidant effects on different skin parameters i.e. skin moisture contents, elasticity and surface evaluation of living skin (SELS). Results: The formulation showed statistically significant (p ≤ 0.05) and the base showed insignificant (p > 0.05) effects on skin elasticity and skin moisture contents. There is a significant decline in SELS, skin scaliness (SEsc), skin wrinkles (SEw), skin smoothness (SEsm), and skin roughness (SEr) parameters after application of the formulation. Conclusions: Topical application of the cosmetic emulsion entrapped with Tamarindus indica seeds extract containing various antioxidants exerts potential skin antiaging effects.